Health related quality of life and patient concerns in patients with osteoradionecrosis. Issue 9 (November 2021) - Chieng, C.Y.; Davies, A.; Aziz, A.; Lowe, D.; Rogers, S.N.
Abstract: The number of patients presenting with osteoradionecrosis (ORN) is likely to increase in future and health related quality of life (HRQOL) is a key outcome. This study aimed to report patient concerns and HRQOL in an osteoradionecrosis cohort over 12 years. Patients attended routine follow-up clinics between 2008 to 2020, where patient reported outcome (PRO) assessment was used before consultations as standard practice. The two PROs were the Patient Concerns Inventory (PCI) and the University of Washington quality of life questionnaire (UW-QOL v4). The study sample comprised 109 patients with ORN seen in 445 clinics when PCI and UW-QOL were used. At clinic, patients were in one of six ORN states: before ORN (26 with data), at diagnosis (12), and following treatment either improved (27), progressed (46), stable (63) or resolved (37). Worst HRQOL outcomes were reported in the progressive group with 50% reporting overall QOL as less than good. Pain was a major dysfunction (63%) as was physical and social-emotional functioning and this group reported many PCI issues, median (IQR) 7 (4-11). Kaplan-Meier estimates of survival with 95% CI after diagnosis with ORN were 96% (90-99%) at 12 months, 89% (81-94%) at 24 months and 73% (61-82%) at 60 months. This study indicates that ORN is a chronic condition with long-term survivorship consequences. More data through cohort studies and trials are needed to assist in decision making for individual patients.